Diagnostic efficacy of Fenyo-Lindberg scoring system in patients of acute appendicitis a one-year cross sectional study - Sahu, Kartik; Bellad, Anil P. (International Surgery Journal, 2020)
Background: Diagnostic scores have been found to be very efficient. The present study was taken up to calculate diagnostic efficacy of Fenyo-Lindberg (FL) scoring system in patients of acute appendicitis. Methods: A one-year cross sectional study was done on 100 patients in patients with right lower quadrant pain. Group I had patients with score of -2 and above and group II with score below -2. The groups were compared with histopathological diagnosis. Then, the sensitivity, specificity, positive predictable value (PPV) and negative predictable value (NPV) were calculated. Results: In this study, the males were 52 and females were 48.15 patients, Total leucocyte count (TLC) had more than 14,000 whereas 16 patients had onset of pain in less than 24 hours. 47 patients had vomiting. Tenderness was present in all cases, while rebound tenderness was present in 54% of cases. 98% of patients had progression of pain, whereas migration was seen in 76%. 56% patients had increased pain on coughing. 54 patients had acute appendicitis on histopathology. The study shows that this scoring system has sensitivity of 72% and specificity of 71% in diagnosing acute appendicitis. The PPV was 75% and NPV was 68%. Conclusions: The FL score is an inexpensive clinical tool that may help the diagnosis of acute appendicitis. The results are comparable to previous studies but as the sample size is small, study has to be done in higher sample size to get the data necessary to generalize the findings and the fact that this study was first on this scoring system in India should also be considered.